STUDY OF FERTILITY, MORTALITY, AND MIGRATION IN POPULATION PROJECTION IN NGAWI REGENCY - Chachan Gusti Rawa; Elan Artono Nurdin; Era Iswara Pangastuti; Muhammad Asyroful Mujib (MAJALAH PEMBELAJARAN GEOGRAFI, 2020)
Ngawi Regency is the westernmost district in East Java province which is directly adjacent to Central Java province. In terms of population in Ngawi Regency, the demographic criteria include size, structure, population distribution, which can change with birth, death, and migration. The absolute population continues to increase, although on the other hand, the growth rate tends to decrease as a result of population policies, either directly or indirectly. The Ngawi Regency area will be able to see its population projection after knowing the fertility, mortality, and migration data which is then overlaid. The purpose of this study is to examine how fertility, mortality, and migration are in population projections in Ngawi Regency.